KARAKTERISTIK BAYI YANG MENDERITA PENYAKIT HIRCSHSPRUNG DI RSUP H. ADAM MALIK KOTA MEDAN TAHUN 2010-2012 - Siska Verawati; Prof. dr. Sori Muda Sarumpaet, MPH; drh. Hiswani, M.Kes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Hirschsprung disease is a cause of lower intestinal obstruction most commonly in neonates (0-28 days), the incidence 1:5000 live births. Hirschsprung disease is more common in males than females with a ratio of 4:1. The mortality rate for Hirschsprung disease ranged from 1-10%. To determine the characteristics of baby suffering from Hirschsprung disease, conducted a research at RSUP H. Adam Malik Medan with case series design. Population and sample was 110 patients in 2010-2012 and recorded in hospital medical records. Univariate data were analyzed descriptively while bivariate data were analyzed using Chi-square, Mann-Whitney, Kruskal Wallis test. Based on sosiodemographic, the highest population is in the age group of 0-28 days (60,0%), male (72,7%%), and came from out of Medan area (85,5%), and referall from Public Hospital District/City (51,8%). Based on the treatment, abdominal distension (56,4%), clinical presentation of abdominal distension, difficult to defecate, delayed passage of meconium (44,5%), test of barium enema (44,6%), medical management of no surgical (59,1%), no complications (80,0%), Jamkesmas (42,7%), the average length of stay 14 days, outpatient control (43,6%). There is a significant differentiation of proportion between age based on medical management (p=0,000), average length of stay based on medical management (p=0,000), medical management based on condition when go home (p=0,000), and average length of stay based on condition when go home (p=0,000). There is no significant differentiation of proportion between age based on sex, complications based on medical management, and average length of stay based on complications. Prognosis of Hirschsprung disease depends on early diagnosed ang surgery approach so that the parents should be given the understanding of the best medical treatment for this disease. Key words : Hirschsprung disease, characterictics of baby, RSUP H. Adam Malik Medan